Diminishing the Pathogenesis of the Food-Borne Pathogen Serratia marcescens by Low Doses of Sodium Citrate - Maan T. Khayat; Samar S. Elbaramawi; Shaimaa I. Nazeih; Martin K. Safo; El-Sayed Khafagy; Mohamed A. M. Ali; Hisham A. Abbas; Wael A. H. Hegazy; Noura M. Seleem (Biology, 2023)
Protecting food from bacterial contamination is crucial for ensuring its safety and avoiding foodborne illness. Serratia marcescens is one of the food bacterial contaminants that can form biofilms and pigments that spoil the food product and could cause infections and illness to the consumer. Food preservation is essential to diminish such bacterial contaminants or at least reduce their pathogenesis; however, it should not affect food odor, taste, and consistency and must be safe. Sodium citrate is a well-known safe food additive and the current study aims to evaluate its anti-virulence and anti-biofilm activity at low concentrations against S. marcescens. The anti-virulence and antibiofilm activities of sodium citrate were evaluated phenotypically and genotypically. The results showed the significant effect of sodium citrate on decreasing the biofilm formation and other virulence factors, such as motility and the production of prodigiosin, protease, and hemolysins. This could be owed to its downregulating effect on the virulence-encoding genes. An in vivo investigation was conducted on mice and the histopathological examination of isolated tissues from the liver and kidney of mice confirmed the anti-virulence activity of sodium citrate. In addition, an in silico docking study was conducted to evaluate the sodium citrate binding ability to S. marcescens quorum sensing (QS) receptors that regulates its virulence. Sodium citrate showed a marked virtual ability to compete on QS proteins, which could explain sodium citrate’s anti-virulence effect. In conclusion, sodium citrate is a safe food additive and can be used at low concentrations to prevent contamination and biofilm formation by S. marcescens and other bacteria.